2019
DOI: 10.1108/jfra-08-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative impacts of mandatory integrated reporting

Abstract: Purpose This paper aims to examine the impact of the 2011 mandatory introduction of integrated reporting (<IR>) on the financial performance, risk and institutional shareholding of listed companies in South Africa to assess whether there is a benefit to <IR> and which may encourage greater adoption of it globally. It contrasts the results with two other African stock exchanges (Nigeria and Egypt with no mandatory <IR>) and examines whether <IR> quality also has an impact on these and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 56 publications
3
28
0
5
Order By: Relevance
“…Akisik and Gal (2019) reported a positive link between IR adoption, stock price growth, ROE and ROA. Firm risk (Conway, 2019) and leverage (Lemma et al, 2019) are also lower alongside IR adoption in the mandatory South African setting; a positive effect on firm value is thus assumed. IR adoption also leads to improved CSR performance (Loprevite et al, 2018).…”
Section: Total Performance Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Akisik and Gal (2019) reported a positive link between IR adoption, stock price growth, ROE and ROA. Firm risk (Conway, 2019) and leverage (Lemma et al, 2019) are also lower alongside IR adoption in the mandatory South African setting; a positive effect on firm value is thus assumed. IR adoption also leads to improved CSR performance (Loprevite et al, 2018).…”
Section: Total Performance Measuresmentioning
confidence: 99%
“…IR adoption also leads to improved CSR performance (Loprevite et al, 2018). Conway (2019), based on a South African setting, concluded that there was a negative relationship between IR adoption, IR quality, and financial performance, while there was a positive relationship between IR quality and CSR performance.…”
Section: Total Performance Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR system has economic implications based on the results of previous studies (Akker, 2017;Barth et al, 2016;Conway, 2019;Zhou et al, 2017;Zúñiga et al, 2020). Companies implementing IR systems will have an impact on the increase in value creation and transparency (Conway, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Non-financial information adds value to the quality of information needed by investors and stakeholders, regarding a company's ability to manage its resources. According to Akker (2017) and Conway (2019), traditional financial reporting does not adequately explain the economic implications of innovation in a company's business activities. Therefore, to complement financial information, the non-financial information disclosed by the company will at least elicit a response from stakeholders.…”
Section: Introductionmentioning
confidence: 99%